Differentiating Burnout from Depression: Personality Matters! - Melchers, Martin Christoph; Plieger, Thomas; Meermann, Rolf; Reuter, Martin (Frontiers in Psychiatry, 2015)
Stress related affective disorders have been identified as a core health problem of the 21st century. In the endeavor to identify vulnerability factors, personality has been discussed as a major factor explaining and predicting disorders like depression or burnout. An unsolved question is whether there are specific personality factors allowing differentiation of burnout from depression. The present study tested the relation between one of the most prominent, biological personality theories, Cloninger’s Temperament and Character Inventory (TCI), and common measures of burnout (Maslach Burnout Inventory General) and depression (Beck Depression Inventory 2) in a sample of German employees (N=944) and a sample of inpatients (N = 425). Although the same personality traits (harm avoidance and self-directedness) were predominantly associated with burnout and depression, there was a much stronger association to depression than to burnout in both samples. Besides, we observed specific associations between personality traits and subcomponents of burnout. Our results underline differences in the association of burnout vs. depression to personality, which may mirror differences in scope: While symptoms of depression affect all aspects of life, burnout is supposed to be specifically related to the workplace and its requirements. The much stronger association of personality to depression can be important to select appropriate therapy methods and to develop a more specified treatment for burnout in comparison to depression.